Obstáculos epistemológicos no estudo do calor - RIBEIRO, Elinete Oliveira Raposo (2004)
The intention of this work is to identify epistemological obstacles in the process of construction of related physical concepts to the heat, from the epistemology of Gaston Bachelard. The research was developed, having as public target, students of third series in the average education of a public school of Belém. For the identification of epistemological obstacles, a questionnaire of opened answers was elaborated, which was applied, first in a group, objectifying the validation of the inquiry instrument. This test, guided the reformulation of the questionnaire for future application in other groups. The answers make possible three different strategies of analysis: in the first one it was focused presence of epistemological obstacles without restricting students or questions, from which it was identified the presence of substantiality obstacle, first experience, verbal, realistic and animistic common knowledge; second it was guided to detect epistemological obstacles disclosed by each student, in all the set of questions, where we verify the presence of at least one epistemological obstacle in the set of answers of each student; third it searched to relate each question (topical) with the corresponding epistemological obstacles, where we verify that the obstacles of the first and substantiality experience were present in answers of almost all the boarded topics, and the obstacles of, verbal, realistic and animistic the common knowledge, are present in lesser frequency. In the attempt to contribute with the improvement of Physics Education, the work shows some suggestions to the theacher, searching the overcoming of these obstacles for the students.